Investigating the Relationship Between Financial Abuse and Mental Health Among Aldery Population In Shahre-Kord - Pari Kiani; Minoo Mottaghi; Arash Ghoddoosy (University of Social Welfare & Rehabilitation Sciences, 2019)
Objectives: In the last decade, researchers have studied factors and conditions related to psychological health in older people. Financial abuse is one of the factors associated with psychological health of older people. The present study was conducted to investigate the relationship between financial abuse and mental health in older people living in Shahr-e Kord City, Iran. Methods & Materials: This a descriptive-correlational study, conducted on 350 older people referring to health centers in Shahr-e Kord City. The study data were collected with Goldberg mental health questionnaire (GHQ-28) and the Persian version of Older Adults Financial Exploitation Measure (OAFEM). The obtained data were analyzed using descriptive and analytical statistics in SPSS v. 22. Results: About (63.1%) of the participants were male, and (36.9%) were female. Also, 30% of the participants had favorable mental health, (37.7%) had moderate mental health, and (32.3%) poor mental health. Finally, (61.4%) of the participants experienced moderate financial abuse and (38.6%) severe financial abuse. There was a significant correlation between mental health and financial abuse (P<0.05). Conclusion: According to the study results, financial abuse affects mental health. Therefore, we suggest that authorities provide proper interventions for increasing older people's awareness of financial abuse and accordingly reducing their financial abuse.